Development of a Non-enzymatic, Non-invasive Sensor for Detection of Lactate in Sweat - ljungh, annie (My University, 2018)
An athlete’s goal is to perform the best way possible and in many cases the level of lactate in blood is an indication of performance possibilities. Blood lactate measurement is conducted to obtain knowledge of the lactate threshold (LT) which is the intensity at which blood lactate starts to increase. Lactate can also be found in sweat and some studies have reported a correlation between lactate in sweat and blood, implying for the possible usage of sweat instead for these types of measurements. Using sweat result in non-invasive measurement, both suitable for the discomfort of the athlete tested and to not affect the training while testing. Most non-invasive sweat sensor are based on degrading of lactate with enzymes and detection with amperometric sensors. For endurance sport, such as marathon’s, an enzyme-based sensor can’t measure for the total performance time without losing effect. The aim of the thesis was to produce a sensory device for evaluating the lactate concentration in sweat. Molecular imprinted polymers (MIP) made of overoxidized polypyrrole (oPPy) using ammonium persulfate ((NH4)2S2O8) as an oxidative agent was successfully drop coated onto screen printed carbon electrodes (SPCE) modified with gold nanoparticles (AuNP). By evaluating the peak current observed by cyclic voltammogram between -0.5 V to -1.5 V at a scan rate 0.05 V/s a decreasing peak could be observed at -1 V to -1.5 V with a higher lactate concentration. By data analysis both with modified and unmodified SPCE-AuNP, showed a linear relationship between lactate concentration and peak current. The electrodes were used to evaluate the lactate level in a real sweat sample. The unmodified electrodes overestimated the lactate level with approximately 10 percent while the modified underestimated by approximately 30 percent.
Keywords: Fysik; Physical Sciences